2004
DOI: 10.1111/j.1443-9573.2004.00169.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing heterogeneity in meta‐analyses of Helicobacter pylori infection‐related clinical studies: a critical appraisal

Abstract: Many methodological flaws were identified in the meta-analyses of H. pylori-related clinical studies, particularly for assessing, reporting and interpreting between-study heterogeneity. This warrants consistent and urgent adherence by reviewers and journal editors to the methodological guidelines for meta-analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 68 publications
(303 reference statements)
1
1
0
Order By: Relevance
“…Interestingly, Espitalier and colleagues 38 reported that 20% of SRs used a random-effects model and 59% used a fixed effects model. Huang and colleagues 37 found that 61% of studies did not describe the model used during analysis, which is consistent with our findings (n¼79, 38%).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, Espitalier and colleagues 38 reported that 20% of SRs used a random-effects model and 59% used a fixed effects model. Huang and colleagues 37 found that 61% of studies did not describe the model used during analysis, which is consistent with our findings (n¼79, 38%).…”
Section: Discussionsupporting
confidence: 92%
“…We noted some inconsistencies between our results and previous research examining heterogeneity. Huang and colleagues 37 assessed heterogeneity in 38 meta-analyses of Helicobacter pylori. Only 50% of the meta-analyses reported a statistical test for heterogeneity.…”
Section: Discussionmentioning
confidence: 99%